Internal coordination and legitimation strategies: assessing the influence of individual commissioners in the policy formulation process. Issue 1 (2nd January 2017) - Bürgin, Alexander
Abstract: While the Commission's influence on Council decisions has attracted considerable scholarly attention, its internal dynamics are still not well known, in particular regarding the individual entrepreneurship of Commissioners. Aiming to contribute to the literature on the Commission's inner workings, this article draws comparisons between the levels of influence that two Commissioners were able to exert in the course of two legislative drafting processes; one of these efforts resulted in the Commission proposal for a Climate and Energy Framework, and the other aimed at introducing a Smart Border Package. Based on document analysis and interviews, it is argued that the influence of a particular Commissioner is best explained by a combination of institutional and discursive analysis. While low levels of interdepartmental coordination serve to increase the discretion of Commissioners, their level of influence also depends on their ability to justify their position with value-based arguments.